Anaesthesia for transcatheter aortic valve implantation (TAVI): An anaesthetist’s perspective - Vivier, R. (SA Heart Journal, 2017)
There are several reviews of anaesthesia for transcatheter aortic valve implantation (TAVI) in the literature. This article refl ects the practice of one South African TAVI unit (Cape Mediclinic unit) based on our experience with 70 TAVI procedures. TAVI should never be regarded as a minor procedure. Patients selected for TAVI all have severe aortic stenosis (AS) and, by selection criteria, represent high risk for surgical aortic valve replacement. The salient points of anaesthesia management for TAVI are pre-operative assessment, haemodynamic management, anti-coagulation management and the detection of procedural complications.